RANCANG BANGUN APLIKASI PENYEWAAN LAPANGAN FUTSAL BERBASIS ANDROID - Dwi Ratnasari; Hayatulloh Firman Hadi; Jian Budiarto (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2018)
Futsal lease nowadays is mostly managed manually. The consumers have to come to the site to check the available schedule and to lease it. It is not effective since it spent times. As the technology advances, an android-based application for futsal lease is alternative solution. The design and development of android-based application for futsal lease use waterfall method which started with design, analysis, development, tryout and implementation. The application provides real time information about futsal court, a search feature to available futsal schedules, futsal leases, and the down payment directly in the application. Based on the results of tryout through questionnaire filled by futsal owners (3 subjects) and consumers (17 subjects), 69,7% of the respondents very agree on the use of the application. Thus, the research concludes that android-based application for futsal lease has satisfied the need of futsal owners and consumers.